2013
DOI: 10.1371/journal.pone.0068110
|View full text |Cite
|
Sign up to set email alerts
|

Pig α1-Acid Glycoprotein: Characterization and First Description in Any Species as a Negative Acute Phase Protein

Abstract: The serum protein α1-acid glycoprotein (AGP), also known as orosomucoid, is generally described as an archetypical positive acute phase protein. Here, porcine AGP was identified, purified and characterized from pooled pig serum. It was found to circulate as a single chain glycoprotein having an apparent molecular weight of 43 kDa by SDS-PAGE under reducing conditions, of which approximately 17 kDa were accounted for by N-bound oligosaccharides. Those data correspond well with the properties of the protein pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 51 publications
3
32
0
Order By: Relevance
“…α1AG is in most species a positive acute phase protein, but data on pig are slightly controversial, probably breed‐dependent. Recent evidences suggest that α1AG is a negative acute phase protein in the pig during infection , whereas it has been observed that obese pigs from certain breeds show significantly higher serum levels of α1AG compared to lean counterparts . In humans, the levels of serum α1AG rise with obesity, which is considered as a sign of overweight‐associated low‐grade inflammation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…α1AG is in most species a positive acute phase protein, but data on pig are slightly controversial, probably breed‐dependent. Recent evidences suggest that α1AG is a negative acute phase protein in the pig during infection , whereas it has been observed that obese pigs from certain breeds show significantly higher serum levels of α1AG compared to lean counterparts . In humans, the levels of serum α1AG rise with obesity, which is considered as a sign of overweight‐associated low‐grade inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the levels of serum α1AG rise with obesity, which is considered as a sign of overweight‐associated low‐grade inflammation . Interestingly, levels of this protein have also been identified to be strongly inversely correlated with growth rate in swine in different studies, in the absence of confounding environmental, health and management factors . It is therefore possible that different genetic backgrounds and inflammatory stimuli result in different responses of α1AG.…”
Section: Discussionmentioning
confidence: 99%
“…There is little characterization of monkey AAG in the literature, though it has also been reported to be lower in cynomolgus monkey (0.1 mg/ml) compared to human (30). The conventional pig is the only species where AAG levels have been reported to be higher (1.1-2.5 mg/ml) (14,18) compared to human. However, this finding has not been consistently observed, lower AAG values of 0.24 mg/ml (16) and 0.34 mg/ml (15) have also been reported in the conventional pig.…”
Section: Speciesmentioning
confidence: 99%
“…(Boncela et al, 2001); however, in that study AGP did not interfere with PAI-1 activity. As previously mentioned, serum AGP concentrations increase during late gestation in the pig and are highest at birth (Lampreave and Piñeiro, 1992), then rapidly decline postnatally Heegaard et al, 2013). The interaction of AGP with insulin to reduce insulin-mediated lipogenesis may be especially important in the fetal pig during late gestation when lipid accumulation within adipose tissue is restricted due to the relative unavailability of exogenous lipids and the consequent reliance on glucose for de novo lipogenesis in the fetus (Mersmann, 1974).…”
Section: Agp and Lipogenesis In Neonatal Pigsmentioning
confidence: 97%